Scaling up production of cephalosporin C by Acremonium chrysogenum W42-I in a fermenter using submerged fermentation - Asmaa A. Ibrahim; Ghadir S. El-Housseiny; Khaled M. Aboshanab; Ansgar Stratmann; Mahmoud A. Yassien; Nadia A. Hassouna (AMB Express, 2024)
Abstract Cephalosporins presently stand as the most extensively utilized antibiotic in clinical settings. Acremonium (A.) chrysogenum is the main strain used in the manufacturing of cephalosporin C (CPC), which offers distinct advantages, including a wide-ranging antibacterial spectrum and powerful antibacterial efficacy. Our study aimed to determine the optimal conditions for scaling up the production of CPC from A. chrysogenum W42-I starting with the optimized conditions on the shake flask level obtained from our previous study and utilizing the optimized media (CPC2). The results indicated that an inoculum size equivalent to 1% v/v, aeration at 1 vvm, and an agitation rate of 400 rpm, with controlled pH at 4, were the most favorable conditions for the CPC production using a laboratory fermentor (14 L). The concentration of generated CPC was assessed using two standard curves obtained from agar well diffusion and high-performance liquid chromatography (HPLC). These optimized conditions resulted in a production of 399.52 µg/mL showing a significant increase of approximately 3.4 folds when compared to the unoptimized fermentation run. In conclusion, our findings demonstrated a more favorable time course for CPC production in the fermentor compared to that in the shake flask. Notably, there was a two-fold increase in production within the first three days. Fortunately, the fermentor achieved a noteworthy increase in output, generating 1.598 gm of the CPC within 4 L.